Pengaruh Asosiasi Merek Berdasarkan Fungsi Merek Produk Hand and Body Lotion Citra terhadap Loyalitas Merek di Surabaya - Nindria Untarini (Universitas Negeri Surabaya, 2018)
The research has been conducted in order to investigate which brand association have strongest effects on consumer behavior. Some of these works only adpot a theoretical perspective, without performing an empirical test. Moreover, several of the empirical studies made analyzes the overall relation between brand association and consumer response, without considering the different dimensions of brand association. This research attempts to study the influence of brand associations based on the brand functions through the dimensions of guarantee, personal identification, social identification, and status on brand loyalty in the consumers willingness to brand rebuying, recommend it to others and pay a price premium for the brand. The research was aimed at users of Citra hand and body lotion brand in Surabaya that had bought Lee Cooper jeans maximum in the last six months at stores which sell Citra hand and body lotion product in Surabaya, based on the non-probabilistic purposive sampling. The method of analysis used is Correlation Canonical Analysis, which is part of multivariate analysis. The Primary data were processed using Statistica 6.0 program with 385 sample. The result show that canonical loading test for each canonical variate for both variable set (independent variable and dependent variable) have loading exceeding 0,5. This indicates a high degree of intercorrelation among brand associations based on brand function through dimensions of guarantee, personal identification, social identification, and status on bran loyalty in the consumers willingness to brand rebuying, recommend it to others, and pay a price premium for the brand. Based on, size of the weights, the order of contribution of independent variable to the first variate is guarantee (0,522), and the dependent variable order on first variate is willingness to brand rebuying for the brand (0,842). And from hypotheses test, the results show there is the influences of brand association based on function through the dimensions guarentee, personal identification, social identification, and status (partial and simultant) on brand loyalty in the consumers willingness to brand rebuying, recommend it to others, and , pay a price premium for the brand. Future research would also be interesting to conduct a comprehensive multicategori analysis in order to identify the relative importance of various brand functions in different product categories, the more various sampling techniques and more samples, and selection of other brands so that to represent all users jeans in Surabaya.